Analysis of the Utilization of UBAYA Digital Archives using the Unifield Theory of Acceptance and Use of Technology (UTAUT) (Open Society Conference, 2023)
The power of information technology has ushered us into a new era known as VUCA (volatility, uncertainty, complexity, and ambiguity). The VUCA era demands rapid adaptation to fast-paced changes for individuals and organizations; otherwise, they risk being left behind. The University of Surabaya's (UBAYA) Archiving Unit is one of the archival institutions responding to these changes by implementing and providing digital archiving services. The management of UBAYA's digital archives aims to facilitate easy access, digital preservation, effectiveness, and efficiency. Therefore, it is important to conduct research to understand user responses regarding the utilization of digital archiving systems using the Unified Theory of Acceptance and Use of Technology (UTAUT) method. The research methodology employed is a mixed-method approach with a sequential explanatory design. The findings reveal that the majority of respondents responded positively to the utilization of this digital archiving system, but ongoing development is still needed, particularly in aligning the specific needs of each user based on their respective units of work. Digital archiving provides user-friendly access, necessitating accurate and appropriate provision. This is because archives serve as the foundation for organizational decision-making and policies. Keywords: digital archives, UTAUT, archive information system